Representasi Budaya Jawa dalam Novel Garuda Gaganeswara: Teka-Teki Jalan Lurus Melingkar Karya Ary Nilandari - Karimah, Aisyah Akhlaqul; Siti Kussuji Indrastuti, Novi (Humanis, 2024)
This research aims to examine elements of Javanese culture in the novel "Garuda Gaganeswara Teka-Teki Jalan Lurus Melingkar" (GGTTJLM) using the Circuit of Culture Hall approach and Koentjraningrat Literary Anthropology. As a country rich in cultural diversity, Indonesia holds a rich culture that is the heritage of its people. However, the potential for social divisions can arise if this diversity is not properly understood and monitored. Children's literature, as depicted in Nilandari's work entitled "Garuda Gaganeswara: The Puzzle of a Straight and Circular Road", plays an important role in shaping, reflecting and inheriting the values, norms and traditions of society. This type of research is descriptive qualitative with data collection techniques in the form of phrases, words and discourse. Data collection was carried out through literature study using reading and note-taking techniques. The research results show that the representation of Javanese culture in the novel GGTTJLM reflects local wisdom, including myths about Dewi Sri and Masangin as seen from the perspective of the Circuit of Culture Hall. The identified cultural elements involve community activities in language, knowledge systems, social organization, living equipment and technology systems, livelihoods, religion and art.